Le Omelie Blickling nella produzione omiletica anglosassone - Giuseppe D. De Bonis (Filologia Germanica)
Ms. Princeton, University Library, William H. Scheide Collection 71 transmits a collection of eighteen homilies. For their form and content, the Blickling Homilies have long been considered far from the spiritual guidelines of the Benedictine Renaissance. Moreover they have been concealed by the homiletic collections by Ælfric and Wulfstan. However, the Blickling manuscript has preserved a collection of homilies that testifies to the existence of a lively Old English homiletic tradition before the Benedictine Revival without being in contrast with the Benedictine movement. The Blickling Homilies follow the liturgical year as the Ælfrician homilies do and share some of their sources with Ælfric. This paper illustrates the main data concerning the Blickling Homilies providing a new research basis for future studies and focusing on the peculiarities of the collection